Gambaran Kesejahteraan Psikologis Orang dengan HIV AIDS (ODHA) Dewasa di Yayasan Medan Plus - Laila Putri Putri; Fajar Utama Ritonga (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2026)
Stigma, discrimination, and various forms of social pressure experienced by people living with HIV/AIDS (PLWHA) may affect their psychological well-being. This issue is particularly important because most HIV cases in Indonesia occur among adults of productive age who face various social demands and responsibilities. This study aims to describe the psychological well-being of adult PLWHA at Yayasan Medan Plus. This research employed a descriptive qualitative approach. Seven informants participated in the study, including three adult PLWHA as primary informants, who were selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the psychological well-being of adult PLWHA is reflected in the six dimensions proposed by Ryff and Keyes: self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. The informants demonstrated acceptance of their HIV status, received meaningful support from family and peer supporters, made independent life decisions, utilized available resources, maintained hopes and future goals, and experienced positive changes in their perspectives and awareness of health after diagnosis. Although they continued to experience stigma, discrimination, and fear of rejection, the informants demonstrated the ability to adapt to their circumstances.